Oxaliplatin-associated sarcoid-like reaction masquerading as recurrent colon cancer. Issue 9 (8th September 2020) - Aedma, Surya Kiran; Chidharla, Anusha; Kelting, Sarah; Kasi, Anup
Abstract : A 54-year-old man with stage IV B metastatic colorectal cancer with liver and peritoneal metastasis was treated with cytoreductive surgery (extended left colectomy, right partial hepatectomy, resection of right diaphragm nodule) and perioperative oxaliplatin-based chemotherapy. The patient was cancer-free for 6 months, at which point a surveillance positron emission tomography-CT scan showed metabolically active hepatosplenic lesions and mediastinal and bilateral hilar lymph nodes. An endobronchial ultrasound bronchoscopy-guided fine needle aspiration of the mediastinal and hilar lymph nodes revealed non-necrotising granulomas. The workup was negative for bacterial, fungal or mycobacterial infection, cancer or autoimmune disease. Carcinoembryonic antigen and COLVERA (a circulating tumour DNA liquid biopsy test for the detection of recurrent colon cancer) tests were negative. Subsequently the rare diagnosis of a sarcoidosis-like reaction from oxaliplatin-based chemotherapy was made. Repeat imaging after 3 months showed resolution of the hepatosplenic lesions and lymphadenopathy, alike.